The Influence of Risks on the Performance of E-Business - Ziane, Brahim (2016)
The between research goal of this study was to ascertain the between e-Business risk factors that considerably influence the performance of e-Business organization negatively. This goal was achieved by gathering empirical data and applying several statistical tests. The data were collected via an online questionnaire. Followed by a descriptive analysis and a Kendall's Test was done to analyze the similarities among the different groups. A One-Way ANOVA analysis was conducted to determine the significance of the difference of e-Business risk between groups. A total of six hypotheses with 49 risk factors were posited and tested. Followed by a factorial analysis that consists of extracting 10 components from the initial exhaustive list of risk factors and comes up with innovative classes of e-Business. These classes were named ‘Experience and Knowledge’, ‘Technology and Security’, and ‘Strategy, Governance and Management’. This research relates to the shortage of agreed e-Business risk construct and their association with different e-Business modules that constitutes the key components of e-Business core activities and processes. The six e-Business modules framework proposed in this research with its risk construct were a contribution that search for addressing these insufficiencies. The practitioner could get an insight from this study to help prioritize the e-Business risk and assign a correct probability of occurrence as well as the significance of the risk impact. The e-Business risk construct framework with its six e-business modules used in this research present a limitation in the context that not all e-Business firm or practitioners necessarily get involved with the six e-Business modules, which might influence the respondent perception and risk rating. Some other limitations are the risk that a respondent might give inaccurate answers because of impatience and the quite small sample size. Finally, conducting a qualitative research with the same proposed e-Business framework is an informative study and might provide more in-depth analyses as a potential further research.